Augmented reality in higher education institutions: a study on the applicability of the evaluation model of educational approaches in mobile augmented reality (MAREEA) - Santos, Nycolle Oliveira Souza; Souza Junior, Armando Araújo de (Brazilian Journal of Production Engineering, 2023)
The present article aims to conduct an analysis on Augmented Reality (AR) as an enabling technology in Higher Education Institutions (HEI) and the applicability of the Model for the Evaluation of Educational Approaches in Mobile Augmented Reality (MAREEA) to improve the evaluative quality of Teaching. This is a research method of qualitative approach; which research objective is exploratory developed from a bibliographic and theoretical-conceptual study based on a survey of research in bibliographic sources for analysis and discussion. The MAREEA model has four evaluation factors, namely: usability, engagement, motivation and active learning. Usability refers to how intuitive it is for users to learn how to use and interact with a certain product, that is, how simple it is for a person to use a certain system. Some studies developed applying MAREEA in HEIs have presented an important advance in research on the subject, especially in the mediation process, cognitive development, and improvement of learning techniques. It was observed that AR has been applied to the process of improvement and refinement of educational projects, particularly in technological education, social education, and inclusive education.
Keywords: Augmented reality; Higher Education Institutions; Model for Evaluation of Mobile Augmented Reality Educational Approaches (MAREEA)